2006
DOI: 10.1007/bf03166209
|View full text |Cite
|
Sign up to set email alerts
|

Variations ofg-tensor principal values in reduced [2Fe−2S] cluster of iron-sulfur proteins

Abstract: This article discusses the present status of the theoretical and experimental studies of the electronic structure of the reduced [2Fe-2S] cluster with a special emphasis on the g-tensor variations in the Rieske-type proteins. The necessity of this analysis is dictated by the fact that the changes in the electron paramagnetic resonance line shape of the redueed cluster are broadly exploited as the basis for different mechanistic conclusions in the stmcture-function studies of the bc~/b6f families.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 22 publications
1
11
1
1
Order By: Relevance
“…Both untreated and potassium-ferricyanide-oxidized samples were EPR silent and retained their brownish color, whereas sodium-dithionite-reduced sample rapidly became pale yellow and showed a prominent signal due to a spin-1/2 species with principal g values of 2.042(2), 1.918(5), and 1.889(5) and an average g value of 1.950(4) (Figure 1D). These g values are consistent with a four-cysteine coordinated ferre- doxin-type [2Fe2S] + cluster (Beinert et al, 1997;Liu et al, 2014;Shubin and Dikanov, 2006). Hence, isolated FBXL5 possesses a [2Fe2S] cluster in its oxidized [2Fe2S] 2+ state.…”
Section: Fbxl5 Harbors a [2fe2s] Clustersupporting
confidence: 70%
“…Both untreated and potassium-ferricyanide-oxidized samples were EPR silent and retained their brownish color, whereas sodium-dithionite-reduced sample rapidly became pale yellow and showed a prominent signal due to a spin-1/2 species with principal g values of 2.042(2), 1.918(5), and 1.889(5) and an average g value of 1.950(4) (Figure 1D). These g values are consistent with a four-cysteine coordinated ferre- doxin-type [2Fe2S] + cluster (Beinert et al, 1997;Liu et al, 2014;Shubin and Dikanov, 2006). Hence, isolated FBXL5 possesses a [2Fe2S] cluster in its oxidized [2Fe2S] 2+ state.…”
Section: Fbxl5 Harbors a [2fe2s] Clustersupporting
confidence: 70%
“…In contrast, the vectors r 23 and r 32 , connecting Fe(II) A -Fe(III) B and Fe(III) A -Fe(II) B , respectively, form the angles θ 1 and θ 2 with the vector H o . These angles could be described through the angle θ as16…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the three directions naturally related to the cluster geometry, which is very close to planar, are often considered as the principal direction of the g-tensor, and include the directions coinciding with the Fe-Fe and S-S vectors and the vector normal to the cluster plane. It should be noted however that theoretical considerations, DFT calculations as well as indirect analysis by powder ENDOR of biological [2Fe-2S] clusters in ferredoxins and Rieske proteins have given somewhat confusing contradictions in the assignment of g max , g mid , and g min principal axes along particular molecular directions 18. Moreover, the single-crystal EPR study on the reduced Rieske cluster in the crystalline cytochrome bc 1 complex with the stigmatellin in the Q o -site has demonstrated that the g-tensor principal axes are indeed skewed with respect to the molecular directions of the [2Fe-2S] core by up to 30°–40° 19.…”
Section: Resultsmentioning
confidence: 99%
“…Calculation of ESEEM spectra was carried out by numerical diagonalization of the rotating spin Hamiltonian composed of a hyperfine, nuclear-Zeeman, and nuclear-quadrupole interactions. An algorithm reported in the previous paper was employed for the simulation of the pattern.…”
mentioning
confidence: 99%